Analysing policy-induced effects on the performance of irrigated rice - Touré, A.A.; Groenewald, J.; Seck, P.A.; Diagne, A. (2013)
Improving local rice production capacity is a key element on the agenda of most countries in the West African Economic and Monetary Union (WAEMU). There are several reasons for this drive: (1) the high levels of rice imports, which constitute a burden on the countries' financial resources; (2) the relatively high contribution of the commodity to national food security programmes; (3) income generation for smallholder farm communities; and (4) the contribution of rice to the improvement of nutritional status. The policy analysis matrix approach was used to evaluate the policy-induced effects of the WAEMU common external tariffs on the performance of irrigated rice production systems in Niger. The results show that the irrigated rice production system receives little protection, and that retail rice marketing channels are even less protected. The negative net policy effects indicate that greater incentives are needed for enhanced system performance.